Safety, sensitivity and “distant” epistemic luck - Freitag, Wolfgang (Theoria, 2014)
Prominent instances of anti-luck epistemology, in particular sensitivity and safety accounts of knowledge, introduce a modal condition on the pertinent belief in terms of closeness or similarity of possible worlds. Very roughly speaking, a belief must continue to be true in close possibilities in order to qualify as knowledge. Such closeness-accounts derive much support from their (alleged) ability to eliminate standard instances of epistemic luck as they appear in prominent Gettier-type examples. The article argues that there are new Gettier-type examples which are grounded in “distant” epistemic luck. It is demonstrated that sensitivity and safety theories cannot handle such examples.